Enhancing water recovery performance of transport membrane condenser by different coolants. (August 2022) - Zhang, Yuntao; Lan, Junjie; Huang, Jiguang; Chen, Haiping; Zhang, Heng; Teng, Da
Highlights: LiCl solution was adopted in membrane condenser for water recovery from gas. Recovery performance of pure water and LiCl solution were compared. LiCl solution as coolant could enhance water recovery performance. LiCl solution would deteriorate heat recovery performance. Abstract: Transport membrane condenser (TMC) has been proven an effective device for reclaiming water in flue gas. Ameliorations in device parameters and structure, operation conditions, and membrane properties have been trialed to augment water recovery performance. But research on improving the performance by adopting different coolants is still absent. In this paper, water in simulated gas was captured by a combination of traditional TMC and liquid desiccant. Three types of ceramic membranes with different pore sizes were adopted. The water and heat recovery performances with pure water or LiCl solution as cooling media were compared. The experimental results show that by adopting LiCl solution as coolant, water recovery rates were increased under different experimental conditions, confirming the potency of liquid desiccant for enhancing water recovery performance of TMC. The recovered water flux increased by 26.7% while water recovery rate increased by 17.5 percent points with LiCl solution in high concentration. On the contrary, heat flux recovered by LiCl solution is lower than that recovered by water. Heat transfer driving force and resistances are analyzed to explain the variation in heat flux. The analysis can be a guidance for coolant selection.